Interdependency between Southeast Asia country stock exchange: based on small capital index / Ahmad Shahril Shaharuddin - Shaharuddin, Ahmad Shahril (2015)
The aim of the study is to investigate the association and relationship between Southeast Asia stock exchange which consist of FTSE Bursa Malaysia KLCI small capital index, Indonesia Stock Exchange small capital index, Stock Exchange of Thailand small capital index, Singapore Exchange small capital index and Philippines Stock Exchange small capital index. The study used Correlation Analysis Statistic and Multiple Linear Regression to obtain the research objective. The daily closing price of stock market indices is collected from 3rd April 2006 to 29th April 2015. From the results, it reveals that all of the Southeast Asia market based on small capital index has a significant positive relationship between each market. It means that there are association and relationship exist between Southeast Asia stock exchanges in small capital index. These results further our understanding of the relationship between the stock market in Southeast Asia and should be useful for parties that involve in the stock markets.